A Free Boundary Problem Governed by Nonlinear Degenerate Equations of Parabolic Type (Journal of Partial Differential Equations, 1992)
We consider a free boundary problem connected with non-Newtonian fluid motion, i.e. the flow of power law fluids with the yield stress. We obtain the solution of the relevant approximation problem by means of a parabolic quasi-variational inequality, and then obtain the weak solution of the original problem after a passage to the limit. Finally, we study the regularity of the weak solution.